CREATING VIRAL MARKETING: DISTRIBUTION MECHANISMS AND IMPACT ON BRAND REPUTATION - Yanchuk, Tetiana; Zabolotna, D.V. (SWorld-Ger Conference proceedings, 2024)
The work explores the basics of creating viral marketing, its distribution mechanisms and impact on brand reputation. The key aspects of successful virus campaigns, their impact on consumers and ways to build long-term branding are analyzed. Both positive